ROLE PLAY IMPLEMENTATION THROUGH COMMUNICATIVE APPROACH IN ENGLISH LANGUAGE TEACHING - Qorihah, Dzul Kamalil; Firdhausya, Alina (UIN Sumatera Utara, 2025)
This conceptual article examines how Communicative Language Teaching (CLT) is applied in English language classes, emphasizing the role-playing method as a method of improving speaking abilities. CLT places a strong emphasis on genuine communication with the goal of enhancing students' confidence, accuracy, and fluency. The difficulties and possibilities of using role play as a teaching strategy are covered in the article, along with issues like instructor readiness, class size, learner anxiety, and motivation. Even though effective implementations have demonstrated notable gains in students' speaking skills, a number of studies draw attention to role play's drawbacks, including a lack of preparation, a variety of learner expectations, and poor instructor leadership.According to the results, the success of role play under CLT depends on the teacher's capacity to give precise directions, foster a positive learning environment, and adjust to the needs of each individual student. When used properly, role play helps to promote active engagement and real-world communication. However, in order to make full use of its potential in English language instruction, challenges like student fear and disengagement must be addressed. The article ends with suggestions for improving the use of CLT through role-playing, stressing the value of instructor assistance and specialized teaching techniques to accommodate a range of learning environments.